2019
DOI: 10.1021/acsaem.8b02118
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Stoichiometry Control in Cu2Se Thin Films for Room-Temperature Power Factor Improvement

Abstract: Cu 2 Se thin films provide a promising route toward relatively safe, sustainable and solution processed thermoelectric (TE) modules in contrast to more expensive and toxic materials currently on the market such as Bi 2 Te 3. Cu 2 Se is known in the TE community for its high performance at high temperature and has recently attracted attention from its large theoretically predicted figure of merit at room temperature. Unfortunately, one of the main limitations encountered so far in Cu 2 Se thin films is that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 72 publications
2
28
1
Order By: Relevance
“…The Se peak shi may be attributed to the change of Se valence state due to the reduction of Cu vacancies and the occupancy of Ag ions within the lattice. 51 The Ag peaks appearing at $369 eV and at $375 eV illustrate a strong presence of Ag within the thin lm sample aer soaking as shown in Fig. 4b.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The Se peak shi may be attributed to the change of Se valence state due to the reduction of Cu vacancies and the occupancy of Ag ions within the lattice. 51 The Ag peaks appearing at $369 eV and at $375 eV illustrate a strong presence of Ag within the thin lm sample aer soaking as shown in Fig. 4b.…”
Section: Resultsmentioning
confidence: 90%
“…48,49,53 To form a thin-lm NC template, we adopted a method developed by Webber et al which demonstrated that bulk copper chalcogenides such as Cu 2 Se, Cu 2 Te and Cu 2 S can be dissolved in a thiol-amine solution mixture and be cast as thin lms on substrates. 45,51,54,55 However, bulk Ag 2 Se powder fails to do so at ambient conditions (see ESI, Fig. S3 †).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, 2D TMDCs have collected a wide attention due to their special properties and are considered to be the next generation of high-performance thermoelectric materials [70,74,90,[175][176][177][178][179][180]. The measured Seebeck coefficient of single-layer MoS 2 can measure over 30 mV K −1 , providing an ideal candidate material for high-performance thermoelectric devices.…”
Section: Thin-film Thermoelectric Materialsmentioning
confidence: 99%
“…In addition, combined with ion beam, laser or photolithography technology, various artificially defined three-dimensional micro-nano structures can be produced, which is convenient for people to understand the relationship between thermoelectric properties and material structure in essence. Many methods have been reported for preparing Cu 2 Se thin films, such as electrochemical deposition [ 21 , 22 , 23 ], pulsed laser deposition [ 24 , 25 ], spin-coating [ 20 , 26 , 27 ], sputtering [ 28 ], thermal evaporation [ 29 , 30 ], etc. For the influence of these preparation methods on the film and the advantages of magnetron sputtering, please refer to our previous article [ 31 ].…”
Section: Introductionmentioning
confidence: 99%